Combined Effect of Inflammation and Hyperglycemia on Mild Cognitive Impairment and Associated Dietary Patterns in an Older Taiwanese Population - Fan, Yen-Chun; Chou, Chia-Chi; Bintoro, Bagas Suryo; Pan, Wen-Harn; Bai, Chyi-Huey (Frontiers in nutrition (Lausanne), 2022)
Previous studies have demonstrated that C-reactive protein (CRP) and glycated hemoglobin (HbA1c) levels are independently associated with neurodegenerative diseases, which can be improved by altering dietary patterns. This study investigates the combined effect of CRP and HbA1c, as well as the influence of dietary patterns, on the risk of dementia. A cross-sectional study was conducted with 536 participants aged ≥65 years who were recruited from the Nutrition and Health Survey in Taiwan between 2014 and 2016. The high levels of inflammation and glycation were defined as a CRP level of >0.21 mg/dl and a HbA1c level of ≥6.50%, respectively. Mild cognitive impairment (MCI) was evaluated using the Mini-Mental State Examination (MMSE) score. The dietary patterns associated with CRP and HbA1c levels were assessed using the reduced rank regression (RRR). Multivariate logistic regression analysis of both complete and imputed datasets was performed. Participants with high levels of both CRP and HbA1c were associated with the highest odds ratio ( ) of MCI (adjusted [a ] = 3.52; 95% = 3.48, 3.56; < 0.001), followed by a high level of only HbA1c (a = 1.73; < 0.001) and a high level of CRP (a = 1.49; < 0.001). Using the reduced rank regression, an inverse relationship between higher consumption nuts and seeds and lower levels of CRP and HbA1c was found (both factors loading < -0.2). Concerning the combined effect of tertiles among the factor 1 and factor 2 analyzed by dietary patterns, group 1 with both T3 (high tertiles) was associated with the greatest of MCI (a = 4.38; 95% = 4.34, 4.42; < 0.001) using multiple imputation. The combined effect of high levels of inflammation and hyperglycemia was associated with an increased likelihood of MCI. Moreover, dietary patterns positively related to inflammation and hyperglycemia were associated with MCI, while eating nuts and seeds promoted better cognition.